Genetics - Ahluwalia, Karvita B. (New Age International, 2009)
About the Book: Endeavours to make this seemingly difficult subject understandable and enjoyable for the readers. It provides an account of classical and modern genetics with new developments in the field. The scope of each chapter has been broadened enough to provide information on historical landmarks as well as of new facts from current issues of major journals. Chapters on gene transcription, regulation, human genetics, recombinant DNA and genomics have been given special attention to create awareness about future areas in this growing field. Experimental work is supported by methodologie.